An Efficient Blue‐Emission Crystalline Thin‐Film OLED Sensitized by "Hot Exciton" Fluorescent Dopant. Issue 2 (17th November 2022) - Yang, Jingjie; Zheng, Wantao; Hu, Dehua; Zhu, Feng; Ma, Yuguang; Yan, Donghang
Abstract: Crystalline thin‐film organic light‐emitting diodes (C‐OLEDs) can achieve a large light emission and a low Joule‐heat loss under low driving voltage due to the high carrier mobility of the crystalline thin films. However, it is urgent for the C‐OLEDs to improve their external quantum efficiency (EQE). Here, a novel strategy is proposed using a doped "hot exciton" material to sensitize a high PLQY blue emitter in C‐OLEDs. Benefiting from the capability of the "hot exciton" material harnessing triplet/singlet excitons, the C‐OLED exhibits an efficiency breakthrough with a maximum EQE of 6.2%, a much enhanced blue photon output with pure blue emission Commission International de L'Eclairage (CIE) (0.14, 0.15), a low turn‐on/operation voltage of 2.6 V(@1 cd m −2 )/3.8 V (@1000 cd m −2 ), and a maximum power efficiency (PE) of 9.4 lm W −1 . This work unlocks the potential of C‐OLEDs for achieving high photon output with high EQE. Abstract : By employing crystalline organic semiconductor as host matrix and doped "hot exciton" material as sensitizer, an efficient crystalline thin‐film blue‐emission organic light‐emitting diode with high photon output and low driving voltage is created.